Transcutaneous Vagus Nerve Stimulation (tVNS) does not increase prosocial behavior in Cyberball - Sellaro, Roberta; Steenbergen, Laura; Verkuil, Bart; van IJzendoorn, Marinus H.; Colzato, Lorenza S. (Frontiers in Psychology, 2015)
Emerging research suggests that individuals experience vicarious social pain (i.e., ostracism). It has been proposed that observing ostracism increases activity in the insula and in the prefrontal cortex (PFC), two key brain regions activated by directly experiencing ostracism. Here, we assessed the causal role of the insula and PFC in modulating neural activity in these areas by applying transcutaneous vagus nerve stimulation (tVNS), a new non-invasive and safe method to stimulate the vagus nerve which has been shown to activate the insula and PFC. A single-blind, sham-controlled, within-subjects design was used to assess the effect of on-line (i.e., stimulation overlapping with the critical task) tVNS in healthy young volunteers (n=24) on prosocial Cyberball, a virtual ball-tossing game designed to measure prosocial compensation of ostracism. Active tVNS did not increase prosocial helping behavior toward an ostracized person, as compared to sham (placebo) stimulation. Corroborated by Bayesian inference, we conclude that tVNS does not modulate reactions to vicarious ostracism, as indexed by performance in a Cyberball game.